(untitled) (Sport and Exercise Psychology, 2025)
Luge, bobsleigh, and skeleton are Olympic disciplines characterized by extreme speeds and high technical precision. Despite their spectacular nature and the critical role of both physical and mental preparation, these sports receive less scientific attention compared to other Olympic disciplines. This chapter examines the participation of sliding sports in the Winter Olympics, highlighting the scarcity of scientific research and reviewing the most recent studies. Research is categorized into biomechanics and aerodynamics, sport psychology and stress management, sleep, and recovery in bobsleigh and skeleton athletes. The aim is to provide an updated overview of scientific developments and identify future research areas to optimize training and performance in these disciplines.